Exploration of Arabic Collocation Patterns in the Indonesia Al-Youm News Corpus - Ilham Fatkhu Romadhon; Muassomah Muassomah; Zakiyah Arifa (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This study investigates the structural and semantic characteristics of Arabic collocations in the Indonesia Al-Youm digital news corpus, a corpus compiled from Arabic-language online news texts reporting Indonesian social, political, cultural, and economic issues. Using Sketch Engine’s Multiword Term extraction feature, the study identifies and classifies the top 100 recurrent multiword units according to their morphosyntactic structures, grammatical functions, and semantic domains. The findings show that Arabic journalistic discourse in this corpus is dominated by nominal constructions, particularly idafah, noun–adjective patterns, and Masdar-based formations. Semantically, the collocations cluster around six domains: media identity and digital technology, politics and diplomacy, social protection and administration, economy and development, tourism, culture, and geography, and proper names. The novelty of this study lies in its corpus-based mapping of Arabic collocation patterns within an Indonesian digital news context, an area that remains underexplored in Arabic corpus linguistics. The results contribute to the description of Arabic journalistic phraseology and provide empirical input for Arabic for Specific Purposes, especially journalistic Arabic and media translation instruction.